Abkhazia in 2015: the main political and socio-economic trends - A. Skakov; V. Novikov (Международная аналитика)
The article examines the political and socio-economic processes in Abkhazia in 2015. Special attention is given signed in November 2014 the Russian-Abkhaz Treaty on strategic partnership. Also examines the political process in Abkhazia, including the confrontation between the authorities and opposition, as well as the formation of new parties, claiming to be the third force. Given the short-term forecast of the situation in the Republic.